"Painful legs and moving toes": the role of trauma. Issue 4 (April 1981) - Schott, G D
Abstract : A new syndrome was recently reported with the descriptive title of "painful legs and moving toes". The present paper describes five patients who developed this syndrome following minor trauma to the legs, which in three patients was attributable to surgery. Various mechanisms that may underlie this unusual combination of severe leg pain with involuntary movements of the toes are discussed, as is the role of previous injury. The possibility is considered that whilst the condition may be generated peripherally, a persistent abnormality of the central nervous system consequently develops.